ETHNOGRAPHY OF COMMUNICATION: MESSAGES ANALYSIS ENCOUNTERED IN CENK BLONK USING DELL HYMES SPEAKING THEORY - Komang Windi Wahana Putra; Ni Nyoman Padmadewi (Undiksha Press, 2023)
This study aims to investigate the messages conveyed in CenkBlonk Shadow Puppet. Descriptive qualitative method was used in this study. The writer selected one of the YouTube videos of CenkBlonk official channel based on two criteria; a) it provided adequate data, b) it had several fields of discussion. The data was collected by firstly watching the video several times then transcribing, translating, and analyzing the data. Dell Hymes’ SPEAKING (setting and scene, participants, ends, act of sequence, key, instrumentalities, norms of interaction and interpretation, and genre) mnemonic in Ethnography of Communication (EC) theory was used to analyze the data. The finding shows that messages are mostly conveyed explicitly by puppet characters in three different fields such as religion, finance, and education. Those messages contained suggestion, advice and moral values in order to be followed by all people. The show also amused the viewer within the messages conveyed in the form of hilarious jokes. Keywords: Messages, shadow puppet, speaking theory, communication, viewer